The Implementation of Project Based Learning in Learning Media Development Courses - Rohmah, Nafilatur (Institut Agama Islam Tarbiyatut Tholabah, 2022)
The ability in the field of learning media development must be possessed by students who are indeed prepared to become educators or expert in the field of learning media development. The aims of this study: (1) to describe the steps for implementing project based learning in the course of developing learning media; (2) describe the results obtained from the application of project based learning in the learning media development course. The research method use in this research is descriptive qualitative. The results of this study: (1) the steps for implementing project based learning begin with planning, namely by preparing lesson plans and preparing learning tools, the process is carried out by giving assignment to students to make papers and examples of learning media development, evaluation is carried out by assessing all the resulting learning media development products; (2) the result of the implementation of the project based learning strategy is an understanding of the materials and products or works resulting from the development of learning media.